Hydrogen Cyanamide: A Chemical to Prepone Natural Budburst Timing of Grapevine Cultivars in Nepalese Context - Poudel, Pragya; Dhakal, Ramila; Atreya, Padma Nath; Sapkota, Rekha; Dahal, Kishor Chandra (Agriculture Development Journal, 2024)
Grapes primarily belongs to mediterranean climate but overtime due to successful vine management practices, its cultivation has been extended to sub-tropics and tropics. In Nepal, grape cultivation has been started about 8 decades ago, and the demand of this crop has been increasing every year. However, the critical challenge of heavy rainfall coinciding with the berry harvest period has limited the production window, necessitating innovative solutions. This study explores the potential of grape cultivation in Nepal by assessing significance of hydrogen cyanamide (HC) application to ensure early and uniform budburst and therefore fruit maturity before monsoon. Winter pruning and HC application at 2-5% concentration has been found effective in preponing budburst and maturity in some grapes varieties ‘Steuben’ and ‘Cabernet Sauvignon’ in Nepal, but the results depend on date and dose of HC application in particular variety and specific growing condition. Application of HC at 2% concentration has resulted in earlier budburst by about 3 weeks in var. Cabernet Sauvignon in Dhading, Nepal. Also, the earlier treatment of HC and pruning in comparison to normal time of pruning (December 15 to January 15) has resulted in earlier and higher budburst and observed fruitfulness in varieties like ‘Steuben’ and ‘Cabernet Sauvignon’ in warm temperate belt of Nepal. Thus, the study concludes the prepone of natural budburst is a must need practice for successful viticulture in terai and mid-hills of Nepal. It also emphasizes the need of more research to optimize the application of HC and ensure its efficacy in advancing budburst and maturity specific to variety and locality. Overall, the findings aim to inspire growers, enhance commercial viability, and contribute valuable insights to the viticulture sector in Nepal.